Analysis of Intracochlear New Bone and Fibrous Tissue Formation in Human Subjects With Cochlear Implants. (Annals of Otology, Rhinology & Laryngology, 2007)
OBJECTIVES: In this study we aimed to evaluate new bone and new fibrous tissue formation in the inner ear following cochlear implantation. METHODS: Twelve temporal bones from patients who underwent cochlear implantation during life were prepared for histologic study. The specimens were reconstructed by both 2-dimensional and 3-dimensional methods. These reconstructions were used to calculate the total volume and distribution of new bone and new fibrous tissue in the cochlea, the number of spiral ganglion cells, and other histopathologic parameters. Clinical data, including the last-recorded word recognition scores, were obtained from the patients' medical records. RESULTS: New bone and new fibrous tissue were found in all 12 specimens, particularly at the site of cochleostomy. There was a significant correlation between overall damage to the lateral cochlear wall and the total volume of intracochlear new tissue (Spearman rho = .853; p = .0004). The total volume of new tissue did not correlate with word recognition scores or spiral ganglion cell counts. CONCLUSIONS: These preliminary results suggest that the degree of damage to the lateral cochlear wall may play an important role in influencing the amount of new tissue formation following cochlear implantation. Intracochlear new tissue does not appear to be an important determinant of performance as measured by word recognition scores or the total number of remaining spiral ganglion cells.